CULTIVATING NOBLE MORALS AMONG STUDENTS OF PRIVATE ISLAMIC SENIOR HIGH SCHOOL TARBIAH ISLAMIYAH IN HAMPARAN PERAK SUBDISTRICT, DELI SERDANG REGENCY - Malik, Mukhlis; Lubis, Sakban; Imran, Zulfi; Devina, Amanda (Proceeding International Seminar of Islamic Studies, 2024)
The Purpose of the Research: Describing and Analyzing Efforts in Cultivating Noble Morals Among Students of Private Islamic Senior High School Tarbiah Islamiyah in Hamparan Perak Subdistrict, Deli Serdang Regency. The Process of Cultivating Moral Values at Madrasah Aliyah Tarbiyah Islamiyah Hamparan Perak: Methods, Supporting Factors, and Challenges. Qualitative Research on Moral Values Cultivation at Madrasah Aliyah Tarbiyah Islamiyah Hamparan Perak. The research results indicate that the implementation of planting moral values at Madrasah Aliyah Tarbiyah Islamiyah Hamparan Perak has been carried out well as expected, reflected in the daily behavior of students, including manners in communicating with teachers, friends, and the surrounding community. Supporting factors include cooperation between the madrasah and the dormitory, as well as collaboration with subject teachers and class advisors. Meanwhile, inhibiting factors include lack of support from families and the environment as well as peer influence among students.